2013
DOI: 10.4209/aaqr.2012.12.0340
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Generating Peaks of Bioaerosols for Laboratory Experiments

Abstract: Bioaerosol concentration peaks are frequently encountered in real-life atmospheres (indoor, outdoor, workplace, etc.), where they can be caused by several factors. However, evolution over time and variability of microbiological pollutant concentrations remain under-documented. The contribution of such peaks in the onset or the worsening of respiratory symptoms -in particular immuno-allergic reactions -has yet to be extensively studied. Although experimental bioaerosol generators are increasingly used, the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…2(a)), indicating the enhancement effects of kaolin clay. In general, bioaerosols generated for laboratory investigations are prepared as a pure solution containing only the test microorganisms (Simon and Duquenne, 2013). Therefore, it might be possible to enhance the generation of test bioaerosols by adding small-size nonfloc-type particles, such as kaolin clay, if the added particles will not affect the quality of the generated bioaerosols.…”
Section: The Enhancement Effect Of Bioaerosols By Kaolin Claymentioning
confidence: 99%
“…2(a)), indicating the enhancement effects of kaolin clay. In general, bioaerosols generated for laboratory investigations are prepared as a pure solution containing only the test microorganisms (Simon and Duquenne, 2013). Therefore, it might be possible to enhance the generation of test bioaerosols by adding small-size nonfloc-type particles, such as kaolin clay, if the added particles will not affect the quality of the generated bioaerosols.…”
Section: The Enhancement Effect Of Bioaerosols By Kaolin Claymentioning
confidence: 99%
“…with the highest percentage contributions to the total microbiota -see above), i.e. from bacteria -staphylococci and enterococci with D ae from ~0.75 µm to ~1 µm, aerobic bacilli (Bacillus genus) and Gram-negative rods with D ae about ~0.8 µm, anaerobic bacilli (Clostridium genus) with D ae between 1.4-1.9 µm, actinomycetal species with D ae from 0.6 µm to 1.1 µm, as well as from fungi -Penicillium species with D ae from ~2.3 µm to ~3 µm, Aspergillus species, and from ~2.1 µm to ~3.6 µm, Cladosporium species with D ae about ~1.8 µm, Fusarium species with D ae between 4.35-6.8 µm [143][144][145][146][147], the size distribution analysis revealed that in case of airborne bacteria: a) the concentrations of bioaerosol particles in poultry house with 42-day-old chickens in all studied aerodynamic fractions, i.e. from 0.65 µm to above 7 µm, significantly augmented the concentrations recorded indoors with 7-day-old chickens, and when the poultry house was empty as well as those noted in outdoor (atmospheric) air (Scheffé tests: P < 0.01-0.001); b) when both 42-day-old and 7-day-old chickens were present indoors, the size distribution step plots had similar courses showing that bacteria in the air appeared mainly in the form of fine aggregates, composed solely of vegetative cells or spores and/or their aggregates with dust particles of D ae between 2.1-4.7 µm; c) when the poultry house was empty (i.e.…”
Section: Trichosporon Asahiimentioning
confidence: 99%
“…having the highest percentage contributions to the total microbiotasee below), i.e. from bacteria -staphylococci and micrococci with d ae from ~0.75 µm to ~1 µm and from fungi -Penicillium and Aspergillus species with d ae from ~2.3 µm to ~3 µm and from ~2.1 µm to ~3.6 µm, respectively [41,42,43], such analysis revealed that bacteria appeared in the air mainly in the form of fine and coarse particulates composed of cells/ spores and/or their aggregates with dust particles, while fungi mainly as single conidia in the aerodynamic size range of 2.1-3.3 µm. If inhaled, bioaerosol composed of such particulates may reach and be deposited in case of bacteria within nasal and oral cavities, trachea, primary and secondary bronchi, in case of fungi within secondary bronchi.…”
Section: Microbiological Contamination Of the Air In Premises Housing...mentioning
confidence: 99%